Review of Management of ART Service Delivery for People Living with HIV/AIDS in Nepal (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
HIV/AIDS epidemic has been gradually spreading in Nepal. It is one of the major public health problems of the nation. Treatment, Care and Support are the critical and essential components of the response to HIV infection and AIDS related morbidity in Nepal. The cross sectional study was carried out at four public and three private Anti Retroviral Therapy (ART) sites during last 6 months of 2006 by selecting public ART sites based on the developmental regions of the country. From institutional set-up, human resources supply and availability of ART medicine's perspectives, the management practices of ART in Nepal is satisfactory. However, services need to be improved to make it more effective and efficient and client friendly, considering the standardization and sustainability of services. Government has targeted to increase the number of certified service delivery points for provision of comprehensive treatment and care services in relation to HIV/AIDS. Hence, in order to achieve the targets with increasing the coverage there is a need to review the management process in established ART service delivery sites. Key Words: HIV/AIDS; Nepal; ART DOI: 10.3126/saarctb.v5i1.3081 SAARC J. Tuber. Lung Dis. HIV/AIDS 2008 Vol.5(1)